Thermodynamic description and simulation of solidification microstructure in the Co-Ti system. (January 2020) - Wu, Liying; Zeng, Yinping; Pan, Yafei; Du, Yong; Peng, Yingbiao; Li, Han; Liu, Shuhong; Zhang, Ligang; Liu, Libin
Highlights: Experimental clarify the invariant eutectic equilibrium among liquid, C36 and L12 . Thermodynamic optimization of Co-Ti system. Scheil solidification simulation was employed to analyze the experimental microstructure of as-cast alloys. Good agreement between calculation and experimental data is reached. Abstract: The Co-Ti binary system has been investigated by means of experimental measurements and thermodynamic calculations. In order to provide new phase relationship in the Co-Ti system, 9 key alloys were prepared by arc melting under vacuum. All alloys were examined for phase and composition analysis by means of X-ray diffraction and electron probe microanalysis after annealing at 900 °C for 60 days and 1000 °C for 30 days, respectively. The invariant equilibrium among liquid, L12 and C36 Laves phases was experimentally determined to be an eutectic with the reaction temperature at 1154 °C. A revised Co-Ti phase diagram is presented according to the present experimental results and reliable literature data. A consistent set of thermodynamic parameters for the Co-Ti system was then obtained by means of CALPHAD (CALculation of PHAse Diagram) approach. The present thermodynamic parameters can describe the experimental results satisfactorily. Scheil solidification simulation was employed to analyse the experimental microstructure of as-cast alloys. The calculated mole fractions of the constitution phases in a few key as-cast alloys are in good agreement with the experimental data obtained by the image J software. The present work indicated that the comprehensive application of the thermodynamic calculation and decisive experiment is an efficient strategy to obtain the desired solidification microstructure.